Être cadre dans le secteur de l’éducation spécialisée : Quelle (s) professionnalité (s) dans un contexte de rationalisation de l’action publique ? - Hélène Chéronnet (Sociétés et Jeunesses en Difficulté)
This article considers the ways and means according to which the managerial work with professionals who perform a taste of assistance is changing under the liberal trends of public politics.We are trying to depict the constraints that weigh upon social and medico-social institutions and the effects of the diffusion of a culture of result and of permanent valuation of devices and individuals on the valorization of a new legitimacy as regards managerial practices.We are here questioning the impact of the reference to social work, considered as a relation of service, on the managerial work of the heads and executive officers of social and medico-social institutions and the space left to users in such an outlook.The evolutions in the political and technical management of public offices, the new method of regulating the social issue may comfort the executives in their managerial work with a certain number of paradoxes. We shall to try to show clearly the ways and means according to which “professionalities”3 are reshaping themselves in order to safeguard an identity of trade and to attempt, within the definition of work and its organization, to keep a place to the user in order to continue to thusly to the upholding of social link.